PENGARUH SELF-EFFICACY DAN PERSEPSI PROFESI GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI - Kinanti, Rengganis Arum; Putri, Eka (FKIP Unswagati, 2023)
Objectives The participants in this study are members of the class of 2020 at Panca Sakti University Bekasi's Economic Education Research Program. The purpose of this research is to investigate the influence that one's self-efficacy and perspective of the teaching profession have on one's level of motivation to enter the teaching profession. This study employs a survey or questionnaire approach to quantitative research with an associative approach, using multiple linear regression analysis to analyze the resulting data. A total of 104 students were selected at random for this analysis. According to the results, an individual's self-efficacy had a more significant influence on their interest in entering the teaching profession than did their perception of the teaching profession itself. If a person is interested in becoming an educator, one factor that goes into the decision-making process is how they feel about themselves in relation to the teaching profession and how confident they are in their abilities.